Types of Control, Ethical Work Climates, and Organizational Citizenship Behavior in the Work-from-Home Setting: Lesson Learned from the Covid-19 Pandemic - Mursita, Lufi Yuwana; Mustafida, Nurul; Rachmadia, Rizki (The Indonesian Journal of Accounting Research, 2023)
The COVID-19 pandemic has encouraged companies worldwide to adjust their working methods using digital technology, especially the work-from-home policy. This paper’s objective is to investigate the effect of the type of management control on organizational citizenship behavior (OCB) in the work-from-home setting, in which the initial design of the job is not intended to be remote. This study also identifies the mediating role of ethical work climates between the two variables. The data are collected through an online survey with 116 respondents of employees working in originally non-remote workplace settings before the pandemic. SmartPLS4.0 is utilized to analyze the data. This study suggests that action control (formal control), personnel control (informal control), and cultural control (informal control) have a positive effect on the ethical work climate. At the same time, the effect further escalates positively to organizational citizenship behavior. Therefore, the ethical work climate fully mediates the three types of control on organizational citizenship behavior. The other finding shows no effect of results control on the ethical work climate. This paper provides evidence that the most effective type of control in involuntary enabled remote working settings is the non-results control or so-called behavioral control. This attempt to reveal the implication of sudden remote working on the effect of control practice on OCBs has not been made by previous research, which makes it the novelty of this research.